Efeitos de resfriamento e espessura no comportamento mecânico de estruturas zircônia-porcelana - Furini, Giordana Picolo (2019)
This study evaluated the biaxial flexural strength (BFS) and failure mode of a zirconia and porcelain in different thicknesses and cooling rates. Zirconia discs were made and covered with porcelain. Samples were divided into 7 groups (n = 30) according to the thickness of the porcelain (1.3 and 2.3 mm), the cooling rate (fast in all layers (RT), slow in all layers (LT), slow in the last layer (LU) and the manufacturer protocol. For fast cooling, the firing chamber was opened after the sintering cycle. For slow cooling, samples were maintained in the oven after the sintering cycle until room temperature. Samples were submitted to mechanical cycling using a flat piston of 3mm, for 5x 105 cycles, 2 Hz, 100N and under 37 ° C water. Samples were tested in biaxial bending keeping the porcelain under tensile stresses until the first signal of fracture (acoustic emission). The failure mode was analyzed. The BFS was calculated and analyzed by 2-way Anova, Tukey (5%), t-test and Weibull. The higher porcelain thickness resulted in lower BFS and lower structural reliability. Cooling did not influence the BFS for specimens with 1.3-porcelain thickness. For 2.3, 2RT presented greater strength than 2LU and 2LT. The predominant failure mode was porcelain crack. A better mechanical behavior of zirconia-porcelain structures is achieved with a thin layer and fast cooling of the layering material.